Measuring the Impact of Bicycle Marketing Messages - Hjuler, Sidsel Birk; Krag, Thomas (Proceedings from the Annual Transport Conference at Aalborg University, 2013)
3,674 responses were received from a survey with several opinion questions on the four transportation modes: bicycle, car, bus and train. Seven different pictures representing marketing messages appeared in the survey. Each of the respondents saw only one picture. The picture was displayed twice on every page of the survey. Respondents were from major Danish cities. Opinions were found to depend on the picture shown, and average opinion scores did in many cases depend on the picture shown in a statistical significant way. A picture of a bicycle accident did increase the average opinion score of cyclists’ general risk as well as the respondents’ experienced self-risk when cycling. The average score of the experienced self-risk was notably lower than the average score of cyclists’ general risk. A picture of a smiling leisure cyclist did raise the average score of cycling experience (enjoyment) and did – to a greater extent – lower the average score of the experience (enjoyment) of the alternatives: car, bus and train. A picture of a bicycle accident and a picture of a cyclist wearing a helmet did raise the average opinion score of other transportation modes (car, bus, train) significantly. This indicates that typical bicycle safety messages has a negative marketing effect on cycling. Opinions on appearance of users of different transportation modes and whether a given transportation mode strengthens or hurts one’s image showed that cyclists are found to look better and that the bicycle gives a better image than any other transportation mode. Pictures also had an impact on opinions here, but the tendencies differed from the opinions on cycling experience, as a picture of a cyclist wearing a helmet did raise average opinion scores of appearance and image for cyclists. A final part of the survey asked directly for opinions on values related to the different pictures. The helmet picture scored higher on all opinions, even on comfort, than a picture of the same cyclist without a helmet. When asked directly respondents are thus in favor of bicycle helmets, but they seem to prefer not using helmets themselves. Further analysis of the data may give deeper insight into this paradox.